A Peptide‐Based Method for the Fabrication of 1D Rail‐Like Nanoparticle Chains and 2D Nanoparticle Membranes: Higher‐Order Self‐Assembly. Issue 4 (4th April 2019) - Wei, Wei; Liu, Yanfei; Xiong, Na; Yu, Limei; Zhang, Tao; Song, Hong; Tang, Fushan
Abstract: Functionalized histidine‐rich peptide sequences were designed for the site‐directed assembly of nanoparticles. TEM and AFM images shown that the peptides self‐assembled into well‐ordered nanofibrils at pH 7.2. The nanofibrils could lie parallel to one another and form membranes when the solution was acidic (pH 3.8) resulting from the hierarchical assembly of the nanofibrils in the direction of the peptide backbone. These peptide structures served as a template for nucleation and growth of Au nanocrystals. Further characterization showed that the Au nanocrystals grew on both sides of the nanofibrils, and a 1D system with a rail‐like structure and a 2D membrane were synthesized after reduction with hydrazine hydrate at neutral and acidic pH values, respectively. The size and packing density of the Au nanocrystals were positively correlated with the incubation time of the Au ions. This approach can be extended further to the controlled synthesis of 1D and 2D architectures formed from metals, metal sulfides, and metal oxides in a low‐cost and simple manner. Finally, the nanostructures could catalyze the reduction of p ‐nitrophenol with rate constants of 0.83±0.14 and 0.69±0.09 min −1 for the 1D and 2D structures, respectively. Abstract : On the rails : Self‐assembled peptides can be used for the template‐directed synthesis of 1D rail‐like Au nanoparticle chains and 2D nanomembranes. The resulting nanocomposites could catalyze the reduction of p ‐nitrophenol. The peptide may be used as a template to nucleate and grow various types of nanocomposites from other metals, or metal sulfides or oxides.